Profile of Patients Visiting a Tertiary Eye Hospital and their Perception Regarding Barrier for Eye Care Services in the Western Saudi Arabia - Magliyah, Moustafa; Alsaedi, Ali; Alqahtani, Nawwaf; Almalki, Mohammed; Alharthi, Adel; Qutub, Weam; Khandekar, Rajiv (International Journal of Medical and Health Sciences Research, 2017)
Introduction: King Abdullah Medical City (KAMC) is a tertiary health care hospital in western Saudi Arabia. We present the profile of eye patients visiting this institution and their perceived barriers for the access to eye care. Methodology: This case series type of study was conducted between January and June 2014. Close-ended questions were used to collect the responses of patients. Results: Our series had 165 eye patients. The proportion of male and female population in the study area was 57:43. The sex ratio of eye patient was 59:41. Sixty patients (37%) needed more than one-hour car-drive to reach hospital. Majority of eye patients were referred from Al-Noor specialist hospital 53(32%) and Hiraa General Hospital 40 (24%) of Makkah. Conclusion: Eye patients of KAMC reside mainly in Makkah. Female gender was not while distance was a barrier for accessing tertiary eye care. The workload in eye unit of KAMC was low.